Transcriptional Activation of the Integrated Chromatin-Associated Human Immunodeficiency Virus Type 1 Promoter - El Kharroubi, Aboubaker (American Society for Microbiology, 1998)
The regulation of human immunodeficiency virus type 1 (HIV-1) gene expression involves a complex interplay between cellular transcription factors, chromatin-associated proviral DNA, and the virus-encoded transactivator protein, Tat. Here we show that Tat transactivates the integrated HIV-1 long terminal repeat (LTR), even in the absence of detectable basal promoter activity, and this transcriptional activation is accompanied by chromatin remodeling downstream of the transcription initiation site, as monitored by increased accessibility to restriction endonucleases. However, with an integrated promoter lacking both Sp1 and NF-κB sites, Tat was unable to either activate transcription or induce changes in chromatin structure even when it was tethered to the HIV-1 core promoter upstream of the TATA box. Tat responsiveness was observed only when Sp1 or NF-κB was bound to the promoter, implying that Tat functions subsequent to the formation of a specific transcription initiation complex. Unlike Tat, NF-κB failed to stimulate the integrated transcriptionally silent HIV-1 promoter. Histone acetylation renders the inactive HIV-1 LTR responsive to NF-κB, indicating that a suppressive chromatin structure must be remodeled prior to transcriptional activation by NF-κB. Taken together, these results suggest that Sp1 and NF-κB are required for the assembly of transcriptional complexes on the integrated viral promoter exhibiting a continuum of basal activities, all of which are fully responsive to Tat.